2017
DOI: 10.1080/03007995.2017.1364226
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue is more strongly associated with insulin resistance than subcutaneous adipose tissue in Chinese subjects with pre-diabetes

Abstract: Pre-diabetic subjects with insulin resistance had elevated levels of VAT. VAT was more strongly associated with insulin resistance than SAT in Chinese subjects with pre-diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 38 publications
0
40
0
2
Order By: Relevance
“…Increasing evidence suggests that the heterogeneity of fat composition and the distribution of adipose tissue can be crucial in the development of insulin resistance and cardiometabolic disruptions [5658]. Visceral adipose tissue (VAT) has been closely linked to an increasing incidence of insulin resistance [56], T2DM, and a higher risk of cardiovascular disease [59, 60].…”
Section: The Influence Of Obesity On Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that the heterogeneity of fat composition and the distribution of adipose tissue can be crucial in the development of insulin resistance and cardiometabolic disruptions [5658]. Visceral adipose tissue (VAT) has been closely linked to an increasing incidence of insulin resistance [56], T2DM, and a higher risk of cardiovascular disease [59, 60].…”
Section: The Influence Of Obesity On Insulin Resistancementioning
confidence: 99%
“…Visceral adipose tissue (VAT) has been closely linked to an increasing incidence of insulin resistance [56], T2DM, and a higher risk of cardiovascular disease [59, 60]. VAT is associated with a high production of pro-inflammatory adipocytokines, oxidative stress, and renin–angiotensin–aldosterone system (RAAS) activation [61, 62].…”
Section: The Influence Of Obesity On Insulin Resistancementioning
confidence: 99%
“…Thus, relative to Western populations, abdominal adiposity in Asians may play a bigger role in DM development than BMI, which is related to physical stature. Previous studies of Asians have also indicated that abdominal adiposity plays a more significant role in DM and insulin resistance [10,18,32,33]. The present study aimed to address this issue by using VO 2 peak/FFM as the CRF index, rather than VO 2 peak/BW to avoid confounding from obesity.…”
Section: Discussionmentioning
confidence: 96%
“…However, the distribution of adipose tissue is an important risk factor correlated with the onset of metabolic syndrome (5). Several studies have suggested that visceral adipose tissue is metabolically and functionally different from subcutaneous adipose tissue and that visceral adipose tissue demonstrates a stronger association with insulin resistance, metabolic disorders, and cardiovascular risks (6‐8).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies have been performed in subcutaneous adipose tissue because of its easier access, but metabolic health status is more tightly associated with visceral adipose tissue than subcutaneous adipose tissue (6,7,9,12). The mass of visceral adipose tissue is significantly higher in IRO than ISO (6). Moreover, many studies have employed insulin sensitivity as an indicator for metabolic health, but it is noteworthy that insulin sensitivity is not equal to metabolic health.…”
Section: Introductionmentioning
confidence: 99%